Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1371/journal.pone.0140935
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of ROS-Mediated Oridonin-Induced Oesophageal Cancer KYSE-150 Cell Apoptosis by Atomic Force Microscopy

Abstract: High levels of intracellular reactive oxygen species (ROS) in cells is recognized as one of the major causes of cancer cell apoptosis and has been developed into a promising therapeutic strategy for cancer therapy. However, whether apoptosis associated biophysical properties of cancer cells are related to intracellular ROS functions is still unclear. Here, for the first time, we determined the changes of biophysical properties associated with the ROS-mediated oesophageal cancer KYSE-150 cell apoptosis using hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…It has been reported that oridonin could inhibit in vitro or in vivo growth of several human malignancies, such as oral cancer, gallbladder cancer, glioma, pancreatic cancer, cervical cancer . Our previous work also proved that oridonin could induce ROS‐mediated esophageal cancer KYSE‐150 cell apoptosis, but the exact mechanism and the underlying signaling pathway of oridonin on human esophageal cancer remained poorly characterized. In the current study, we aimed to explore the anticancer effects of oridonin and its underlying molecular mechanism in esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oridonin could inhibit in vitro or in vivo growth of several human malignancies, such as oral cancer, gallbladder cancer, glioma, pancreatic cancer, cervical cancer . Our previous work also proved that oridonin could induce ROS‐mediated esophageal cancer KYSE‐150 cell apoptosis, but the exact mechanism and the underlying signaling pathway of oridonin on human esophageal cancer remained poorly characterized. In the current study, we aimed to explore the anticancer effects of oridonin and its underlying molecular mechanism in esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…ROS, mainly produced from the mitochondrial electron transport of aerobic respiration, have a role in regulating cell signaling pathways, including the activation of cell signaling cascades, gene expression, and apoptosis [1819]. A recent investigation found that ROS are implicated in cellular activity to a variety of inflammatory responses [20].…”
Section: Introductionmentioning
confidence: 99%
“…1), is a diterpenoid compound (10). Previous studies have shown that oridonin has antitumor activities in vivo and in vitro (11)(12)(13), and oridonin inhibited proliferation of cancer cells by inducing autophagic pathways (14)(15)(16)(17)(18), arresting the cell cycle on G 0 /G 1 phase (19) or G 2 /M phase (20)(21)(22)(23)(24), inducing apoptosis of human laryngeal cancer cells (25), esophageal cancer (26), colorectal carcinoma (27), pancreatic cancer (28), hepato cellular carcinoma (29,30). However, few reports exist on oridonin-induced apoptosis on gastric cancer.…”
Section: Introductionmentioning
confidence: 99%